Oxidative stress and alopecia areata - Ma, Yi-qian; Sun, Zhan; Li, Yu-Mei; Xu, Hui (Frontiers in Medicine, 2023)
Alopecia areata is an inflammatory autoimmune disease characterized by non-scarring hair loss on the scalp or any other part of the hair-bearing skin. While the collapse of the immune privilege is considered one of the most accepted theories accounting for AA, the exact pathogenesis of the disease remains unclear. Other factors, such as genetic predisposition, allergies, microbiota, and psychological stress, also play a role in the occurrence and development of AA. Oxidative stress, an unbalanced state between oxidation and antioxidant defense systems, is believed to be associated with AA. In this review, we examine the relationship between the pathogenesis of alopecia areata and oxidative stress, as well as the evidence of oxidative stress in AA patients. In the future, antioxidants may play a new role as a supplementary therapy for alopecia areata.